Bacteremia-Induced Cholestatic Jaundice as a Major Manifestation of Pneumococcal Infection in a Healthy Toddler - Suzuki, Shigeru; Taketazu, Genya; Mukai, Tokuo; Sakata, Hiroshi; Oki, Junichi (Journal of Pediatric Infectious Diseases, 2020)
The development of pneumococcal conjugate vaccines has substantially decreased the incidence of invasive pneumococcal diseases. However, the incidence of bacteremia due to nonvaccine serotypes has increased. Therefore, it is important to recognize the symptoms and complications of pneumococcal infection to expedite diagnosis. Herein, we report the case of a 22-month-old patient diagnosed with pneumococcal bacteremia who presented with cholestatic jaundice and fever without any other signs of systemic sepsis. The patient's condition improved soon after antibacterial therapy. Other causes of jaundice were possibly ruled out based on the screening test for viral hepatitis, and there were no abnormal findings on abdominal ultrasonography. Therefore, the present case suggests that cholestatic jaundice could be a manifestation of pneumococcal bacteremia.
Keywords: cholestasis; Streptococcus pneumoniae; bacteremia; jaundice